The Coverage of Jerusalem Issues in ArabicLanguage Satellite TV. Channels; a Comparative Study of Aljazeera, Al Arabiya and Al Alam - H. Shtaiwi, Dr. Mohammed M. (IJRDO - Journal of Social Science and Humanities Research, 2016)
The focus of the study is Jerusalem’s coverage by Arabic–Language Satellite Channels: Aljazeera, Al-Alam and Al-Arabiya as a model represented three trends in the Arab and Islamic world. Jerusalem issues tackled by Arab and non-Arab media, since the occupation of the western part of the city after the withdrawal of the British army from Palestine in 1948, since then the holy city witnessed various forms of violations and abuses every day. These violations and abuses aimed at Judaizing holy sites, confiscating land and houses, expulsion of Palestinians and bringing settlers in to replace them .To achieve the objectives of the study, the researcher analyzed the content of Jerusalem coverage in Aljazeera, AL Alam and Al Arabiya .The study sample consisted of all content: (news, reports, documentaries, live and interviews) of these three channels during 6 months, (period of the study) which is related to the topic. This period started July 1st and ended December 31st, 2010. The dates that the researcher chose were based on constructed weeks (Saturday the first week, Sunday of the second, Monday of the third, etc. So we had 25 days for each channel. Content analysis was the tool used in the study. While conducting the study, the researcher relied on theoretical literature and previous studies. These previous studies were subjected to the validity and verification procedures before applying them to theoretical analysis of all programs in the three channels.The researcher developed the questions as objectives for his study. So the study examined how the three leading Arab Satellite Channels covered Jerusalem issues in their daily activities in term of technical forms, content and time. What were these three channels‟ agenda regarding to Jerusalem issues? How did the three channels reflect their national interest through their new coverage? The study concluded that both Aljazeera and AL alam dealt with the coverage of Jerusalem issues with considerable interest, but Al Arabiya was less interested .The results showed that each channel responded differently to the questions of the study. They dealt with all technical forms but in varying proportions. Aljazeera was in the lead in terms of quantity, while AL alam came first in terms of qualitative. They showed a clear contrast in media concept. The three channels reflected their national interest and the political agenda of the country that funded each. While Al-Jazeera and Al-Alam were more interested in the issues of Judaizing and settling the city, Al Arabiya was interested in the negotiations between the parties. As for the sources, the results showed that Al-Jazeera and Al-Alam depended on the reporter and on the special office as first source, but Al-Arabiya depended heavily on International news agencies. The results confirmed that Media coverage of Jerusalem issues in Al-Jazeera and Al-Alam did not depend on crises events or seasonal coverage and celebration, but it was normal daily news. The study recommended that: The 3 channels had recommended the use of all artistic templates to increase the given period for Jerusalem’s issue and to present full programs on Jerusalem. They also recommended the unifying media items to be in line with the issue, and to stop dealing with Jerusalem‟s issues as seasonal ones, but they should be a solid and fixed part of media institutions in order to face the Israeli propaganda and to focus on the daily life of the Palestinians. AlArabia had recommended increasing attention through covering the settling and Judaizing issues as well as touching the Jerusalemites problems.